Pengembangan Usaha Tani Jagung Terhadap Kesejahteraan Masyarakat Bulukunyi Kecamatan Polongbangkeng Selatan Kabupaten Takalar - Nur Indasari; Syamsuddin AB; St. Nasriah (Universitas Islam Negeri Alauddin Makassar, 2024)
This research discusses the development of corn farming towards the welfare of the people of Bulukunyi Polongbangkeng Selatan, Takalar Regency. The main problems in this research are; 1). What is the strategy for developing corn farming towards the welfare of the people of Bulukunyi? 2). What are the supporting and inhibiting factors in developing corn farming towards the welfare of the Bulukunyi community? The type of research used is qualitative research. The data collection method is carried out through observation, interviews and documentation. Then the method for determining informants uses purportive sampling. Next, the data analysis used is data collection, data reduction and drawing conclusions. The results of this research show that: (1) the strategies used in developing corn farming in Bulukunyi are; 1. use of technology and show how to use it which aims to make it easier for the community to carry out corn farming, 2. management of harvests aims to open up employment opportunities for the community, 3. planting training which is useful for distinguishing which seeds are good and which are not for planting 4. Pest and disease prevention training which is useful for increasing public knowledge on how to care for corn plants. The development of corn farming has had a good impact on community welfare because it is able to open up employment opportunities for farmers and is able to form farmer groups that are useful for agricultural development in Bulukunyi, South Polongbangkeng District. (2) supporting and inhibiting factors in the development of farming businesses, namely as follows: Supporting factors; 1. Land area, 2. Increasing price of corn, 3. Formation of farmer groups. Inhibiting factors, 1. Pests, 2. Scarcity of subsidized fertilizer, 3. Lack of capital when carrying out corn farming.